만성 뇌졸중 환자들의 Step Test의 상대적·절대적 신뢰도와 타당도 - 이병권; 최현수; 안승헌; Lee, Byoungkwon; Choi, Hyunsoo; An, Seungheon (Journal of the Korean Society of Integrative Medicine, 2017)
Purpose : To examine the relative absolute reliability and validity of step test (ST) scores in subjects with chronic stroke. Method : A total of 27 stroke patients, participated in the study. A relative reliability index (intraclass correlation coefficient, ICC) was used to examine the level of agreement of inter-rater test-retest reliability for ST score. Absolute reliability indices, including the standard error of measurement(SEM) and the minimal detectable change (MDC), and limits of agreement by Bland and Altman analysis. The validity was demonstrated by spearman correlation of ST score with 10 m Walk Test (10mWT), Fugl-Meyer Assessment-Lower/Extremity (FMA-L/E)-total score, Berg Balance Scale (BBS)-total score. Result : An excellent inter-rater reliability in ST scores was found (paretic, ICC=0.993~0.996; nonparetic, ICC=0.982~0.991). In addition, excellent test-retest reliability was found (paretic, ICC=0.992; nonparetic, ICC=0.967). It all showed acceptable SEM of the ST score as paretic and nonparetic were 0.22 and 0.46 respectively (average score <10 %), and the MDC of the paretic and nonparetic were 0.61 and 1.27 respectively (possible highest score <20 %). indicating that measures had a small and acceptable measurement error. The ST score of paretic and nonparetic were also found to be significantly associated with 10MWT (r=0.77~0.79), FMA-LE scores (r=0.73~0.81) and BBS scores (r=0.72~0.76). Conclusion : The ST showed highly sufficient Inter-rater test-retest agreement and validity and acceptable measurement errors caused by due to chance variation in measurement. It also can be used by clinicians and researchers to assess the balance and mobility performance and monitor functional change in chronic stroke patients.